2016
DOI: 10.1007/978-3-319-48743-4_28
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Enterprise and Software Engineering Through an User-Centered Design Perspective

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. Abstract. The development of Web-based Information Systems is crucial in the quest to maintain and develop the enterprise competiveness. However, capturing requirements from Business Processes (BP) is still an issue, as existing methods mostly focus, or on human aspects and the user interface, or on business concerns as rules and workflow coordination, and therefore do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…As can be seen from the obtained results, the most relevant features are the following: rule-based, changes at run-time, context-sensitive, and DBP feasibility. The importance of the rule-based feature can be explained by the phenomenon that BRs are widely agreed between researchers and practitioners as a way to express business knowledge and govern BP ( Valente et al, 2016a , 2016b ; Vasilecas, Kalibatiene & Lavbič, 2016 ). Consequently, there is a number of researches appling busyiness rules for ensuring BP dynamicity.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from the obtained results, the most relevant features are the following: rule-based, changes at run-time, context-sensitive, and DBP feasibility. The importance of the rule-based feature can be explained by the phenomenon that BRs are widely agreed between researchers and practitioners as a way to express business knowledge and govern BP ( Valente et al, 2016a , 2016b ; Vasilecas, Kalibatiene & Lavbič, 2016 ). Consequently, there is a number of researches appling busyiness rules for ensuring BP dynamicity.…”
Section: Resultsmentioning
confidence: 99%
“…Authors [4,9,10,28] found that BR specifically prepared for the project positively affect software implementation project success because they can help in specifying requirements, software design, software architecture and creating test cases.…”
Section: Rq2mentioning
confidence: 99%
“…The impact of BR on enterprise software implementation project success has been argued in several software disciplines, such as requirements specification [3][4][5][6], software quality assurance [7], software evolution [8], business modelling [9,10], etc. Moreover, Lal [4] claims that BR are relevant to the entire software project life cycle.…”
Section: Introduction 1problem Statementmentioning
confidence: 99%
“…In different contexts from those investigated by our approach, studies have also been conducted to explore the use of BDD as part of empirical analysis of acceptance test-driven development [26]. Other studies have concentrated in the use of automated acceptance testing to support BDD traceability [21], or in analyzing its compatibility with business modeling [8], [9], enterprise modeling [47], [48], [46] and with BPMN [23].…”
Section: Related Workmentioning
confidence: 99%